2009
DOI: 10.1002/ibd.20939
|View full text |Cite
|
Sign up to set email alerts
|

Resource use and societal costs for Crohnʼs disease in Sweden

Abstract: Patients in remission have the lowest costs and the highest HRQoL. Patients responding to treatment have lower costs of care than patients with high disease activity who are not treated or do not respond to treatment. Thus, total costs of care might be reduced by efficient treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…However, only absenteeism among patients with occupational activity and loss of leisure time among unemployed patients were included in the study [4]. Mesterton et al [45] estimated the indirect cost of CD in Sweden at €465 per patient per four weeks (absenteeism and presenteeism), which was nearly two times higher than that in our study (€250.48).…”
Section: Discussionmentioning
confidence: 64%
“…However, only absenteeism among patients with occupational activity and loss of leisure time among unemployed patients were included in the study [4]. Mesterton et al [45] estimated the indirect cost of CD in Sweden at €465 per patient per four weeks (absenteeism and presenteeism), which was nearly two times higher than that in our study (€250.48).…”
Section: Discussionmentioning
confidence: 64%
“…All of the identified studies estimated costs that resulted from absenteeism. Only two papers also included those costs that resulted from presenteeism [12,16]. In one study, This systematic review discovered a great range of costs, from US$515.67 per year per patient [27] to US$14,727.05 per year per patient [20] for scenario 1 and from US$532.99 per year per patient [27] to US$ 25,194.92 per year per patient [12] for scenario 2.…”
Section: Resultsmentioning
confidence: 98%
“…† absenteeism only, presenteeism only and for studies considering both absenteeism and presenteeism as those two phenomena are incomparable. Unfortunately, out of the two studies concerning presenteeism [12,16], only one of them [12] presented enough data to be eligible for meta-analysis; therefore, such analysis was not performed, and meta-analysis was performed only for studies concerning absenteeism. Only those studies that presented the number of patients, mean costs and standard deviation (standard error or confidence intervals), or those that made it possible to easily calculate such data were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that patients with CD present significant absenteeism and reduced productivity 3,31,32 ; others have shown that indirect costs derived from lost productivity may be even greater than those from direct health care costs and that these costs increase proportionally with the severity of the disease. 33,34 A meta-analysis including 1020 patients with CD treated with adalimubab showed a major improvement in productivity and therefore a decrease in indirect costs. 35 Thus, the availability of a shortened questionnaire on perceived work disability might help to determine the impact of different treatments.…”
Section: Discussionmentioning
confidence: 99%